Vibration Characteristic of High-Voltage Tower Influenced by Adjacent Tunnel Blasting Construction. (22nd May 2019) - Duan, Limin; Lin, Wenshuai; Lai, Jinxing; Zhang, Peng; Luo, Yanbin
Abstract : The effects of tunnel blast excavation on the adjacent existing high-voltage tower are comprehensively studied for the Chashan highway tunnel project as a case study. To investigate the effect of blast-induced vibration from the tunnel on the adjacent existing tower, field tests and numerical simulations method were adopted to study the vibration velocity and vibration frequency of the existing tower. Moreover, the relationship between the transverse distance from the detonation center and the peak velocity is discussed in detail. The results showed that the peak velocity of the measuring point in tower foundation increases with the distance between the detonation center and tower foundation approaches, and the maximum velocity is appearing when detonation center is 0 m. Furthermore, the corresponding energy spectrum distributions of the existing tower under the effect of blast induced by vibration is also analyzed, and the main frequency of vertical vibration is generally higher than that of transverse vibration. On combining the peak velocity with the main frequency and the natural frequency of the tower, the safety evaluation of the blasting area is proposed, and the corresponding control measures of blasting vibration are put forward. A guideline for the blast safety zone is proposed based on vibration velocity, main frequency, and the quantity of explosive.